Economic Factors Affecting Foreign Direct Investment in Thailand - Li, Phaksuwan; Onsumlee, Natcha; Soontarodom, Dacharthon; Chomkhunthod, Thitipong; Tachasaen, Dr.Tanes (Journal of KMITL Business school, 2023)
This study aims to (1) examine economic factors affecting foreign direct investment in Thailand and (2) investigate the relationship between economic variables affecting foreign direct investment in Thailand using time-series secondary data. The data is annual and spans from B.E. 1997 to 2565. We will analyze it in the form of a complex regression equation with the least squares method. Independent variables include gross domestic product, inflation, trade balance, minimum labor wage rate, unemployment rate, loan interest rate, exchange rate, and foreign direct investment value in Thailand. The study’s results indicate that gross domestic product has the most significant impact on foreign direct investment in Thailand, followed by inflation and the minimum labor wage rate. These factors are directly related to the value of foreign direct investment in Thailand. The findings from this study can benefit all sectors by improving the direct investment promotion policy to attract more investment to Thailand. It can serve as a guideline to enhance the investment environment in Thailand, such as fostering the development of gross domestic product through infrastructure development, supporting the tourism industry, establishing additional economic zones, and addressing inflation through a combination of monetary policies for financial stability. This includes using policy interest rates in conjunction with tax reductions or increased government spending and enhancing the labor potential in line with rising minimum labor wage rates. This can involve training in foreign languages, especially English, Chinese, and Japanese, to support international collaboration.